Characterization of the Safety and Pharmacokinetic Profile of D-Methadone, a Novel N-Methyl-D-Aspartate Receptor Antagonist in Healthy, Opioid-Naive Subjects: Results of Two Phase 1 Studies. Issue 3 (May 2019) - Bernstein, Galina; Davis, Kelly; Mills, Catherine; Wang, Lu; McDonnell, Michael; Oldenhof, John; Inturrisi, Charles; Manfredi, Paolo L.; Vitolo, Ottavio V.
Abstract: Purpose/Background: N -methyl-D-aspartate (NMDA) receptor (NMDAR) antagonists are potential agents for the treatment of several central nervous system disorders including major depressive disorder. Racemic methadone, L-methadone, and D-methadone all bind the NMDAR with an affinity similar to that of established NMDAR antagonists, whereas only L-methadone and racemic methadone bind to opioid receptors with high affinity. Therefore, D-methadone is expected to have no clinically significant opioid effects at therapeutic doses mediated by its NMDAR antagonism. Methods: We conducted 2 phase 1, double-blind, randomized, placebo-controlled, single- and multiple-ascending-dose studies to investigate the safety and tolerability of oral D-methadone and to characterize its pharmacokinetic profile in healthy opioid-naive volunteers. Results: D-Methadone exhibits linear pharmacokinetics with dose proportionality for most single-dose and multiple-dose parameters. Single doses up to 150 mg and daily doses up to 75 mg for 10 days were well tolerated with mostly mild treatment-emergent adverse events and no severe or serious adverse events. Dose-related somnolence and nausea occurred and were mostly present at the higher dose level. There was no evidence of respiratory depression, dissociative and psychotomimetic effects, or withdrawal signs and symptoms upon abrupt discontinuation. An overall dose-response effect was observed, with higher doses resulting in larger QTcF (QT interval corrected using Fridericia formula) changes from baseline, but none of the changes were considered clinically significant by the investigators. Mild, dose-dependent pupillary constriction of brief duration occurred particularly at the 60-mg dose or above in the single-ascending-dose study and at the dose of 75 mg in the multiple-ascending-dose study. No detectable conversion of D-methadone to L-methadone occurred in vivo. Conclusions: These results support the safety and continued clinical development of D-methadone as an NMDAR antagonist for the treatment of depression and other central nervous system disorders. Abstract : Supplemental digital content is available in the text.